Antibacterial potency of different deposition methods of silver and copper containing diamond-like carbon coated polyethylene. Issue 1 (December 2016) - Harrasser, Norbert; Jüssen, Sebastian; Obermeir, Andreas; Kmeth, Ralf; Stritzker, Bernd; Gollwitzer, Hans; Burgkart, Rainer
Abstract Background Antibacterial coatings of medical devices have been introduced as a promising approach to reduce the risk of infection. In this context, diamond-like carbon coated polyethylene (DLC-PE) can be enriched with bactericidal ions and gain antimicrobial potency. So far, influence of different deposition methods and ions on antimicrobial effects of DLC-PE is unclear. Methods We quantitatively determined the antimicrobial potency of different PE surfaces treated with direct ion implantation (II) or plasma immersion ion implantation (PIII) and doped with silver (Ag-DLC-PE) or copper (Cu-DLC-PE). Bacterial adhesion and planktonic growth of various strains ofS. epidermidis were evaluated by quantification of bacterial growth as well as semiquantitatively by determining the grade of biofilm formation by scanning electron microscopy (SEM). Additionally silver release kinetics of PIII-samples were detected. Results (1) A significant (p  < 0.05) antimicrobial effect on PE-surface could be found for Ag- and Cu-DLC-PE compared to untreated PE. (2) The antimicrobial effect of Cu was significantly lower compared to Ag (reduction of bacterial growth by 0.8 (Ag) and 0.3 (Cu) logarithmic (log)-levels). (3) PIII as a deposition method was more effective in providing antibacterial potency to PE-surfaces than II alone (reduction of bacterial growth by 2.2 (surface) and 1.1 (surrounding medium) log-levels of PIII compared to 1.2 (surface) and 0.6 (medium) log-levels of II). (4) Biofilm formation was more decreased on PIII-surfaces compared to II-surfaces. (5) A silver-concentration-dependent release was observed on PIII-samples. Conclusion The results obtained in this study suggest that PIII as a deposition method and Ag-DLC-PE as a surface have high bactericidal effects.